2003
DOI: 10.1002/hbm.10153
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain mapping during free viewing of natural scenes

Abstract: Abstract:Previous imaging studies have used mostly perceptually abstracted, idealized, or static stimuli to show segregation of function in the cerebral cortex. We wanted to learn whether functional segregation is maintained during more natural, complex, and dynamic conditions when many features have to be processed simultaneously, and identify regions whose activity correlates with the perception of specific features. To achieve this, we used functional magnetic resonance imaging (fMRI) to measure brain activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
223
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(239 citation statements)
references
References 43 publications
15
223
0
1
Order By: Relevance
“…Another temporal region (parahippocampal gyrus) that had previously been found to be sensitive to pictures of buildings and spaces responded selectively when establishing shots or other wide-angle views were presented. This paradigm established that these areas, which previously had been explored using highly controlled picture judgment tasks, responded selectively in the context of realistic dynamic movies (see also Bartels & Zeki, 2004).…”
Section: Sensory Inputs and Perceptual Processingmentioning
confidence: 82%
“…Another temporal region (parahippocampal gyrus) that had previously been found to be sensitive to pictures of buildings and spaces responded selectively when establishing shots or other wide-angle views were presented. This paradigm established that these areas, which previously had been explored using highly controlled picture judgment tasks, responded selectively in the context of realistic dynamic movies (see also Bartels & Zeki, 2004).…”
Section: Sensory Inputs and Perceptual Processingmentioning
confidence: 82%
“…Indeed, it has been shown experimentally that the intensity with which each of these features is perceived correlates linearly with the intensity of activity in the regions specialized for each feature [203]. Moreover, it was shown consistently across subjects that the maximum activity of areas with known specialization correlated with the presence of the corresponding feature [204].…”
Section: Global Versus Local Cortical Processingmentioning
confidence: 93%
“…Indeed, it has been shown that a set of 'feature extracting neural assemblies' decompose in parallel the complex stimulus into so-called fragments of sensation: distinct neuronal assemblies have a preference to process distinct features (a preference for color, shape, motion, smell, etc.) [201,203]. biochemical nature [6]; (c) noncorrelated or only weakly correlated with cognition, behavior, and consciousness levels: For example, it tends to vary insignificantly in awake, sleeping, and anesthetized brains [112].…”
Section: Mechanismmentioning
confidence: 99%
“…Because effects in an fMRI study may be influenced by inclusion of a secondary task, our general approach is to understand complex cognitive processes in a natural context, an approach that has been used with auditory narratives (Brennan et al, 2010;Wilson et al, 2008), natural reading (Altmann et al, 2014;Choi et al, 2014;Choi and Henderson, 2015), film viewing (Bartels and Zeki, 2004;Hasson et al, 2004;Nishimoto et al, 2011), and active photograph viewing Stansbury et al, 2013). Here we asked participants simply to read naturally for comprehension.…”
Section: Introductionmentioning
confidence: 99%